Identification of Potential Geotourism Destination in the River Subayang areas of Kampar, Riau, Indonesia - Dwita Martania; Mira Hafizhah Tanjung; Adi Suryadi (UIR PRESS, 2022)
The readiness of an area to be able to develop tourism potential as geotourism is seen from various aspects, including the existing geological heritage, as well as the enthusiasm of the local community which is the main focus in creating good geotourism, while the government acts as the main mover. In Kampar Regency, Riau Province, to be precise in the Sushadow River area, the Rimbang Balling area located in the Kampar Kiri Hulu sub-district, there are natural attractions that the Subayang river passes through, in addition to the river being so clear, upstream we can find a stone wall waterfall, possibly having a waterfall. This paper, shows the potential of geotourism froum various aspects of geomorphology and community life, such as economic, social, cultural and infrastructure and discusses the role of society and sectors as tourism actors in subayang river using the RAP-fish method. Geotourism studies can be drawn from various integrations of existing theories, conceptual analyzes and practices of nature-based tourism and closer collaboration with relevant social sciences so that they can play a role in the promotion of tourism among the public and professionals.